Quality Kilowatts: A Normative-Empirical Framework for Assessing TNC Performance on Sustainable Electricity Provision in Developing Countries. (April 2017) - Wilde-Ramsing, Joseph
The article develops a conceptual approach employing 'modes' of home-country business culture to evaluate how transnational corporations (TNCs) active in electricity provision in developing countries interpret and incorporate internationally recognised normative standards for 'sustainable electricity provision' (SEP) into their own corporate responsibility (CR) policies. Based on a survey of existing SEP norms, qualitative interviews with corporate managers, and analysis of CR materials, the article evaluates how 'quality kilowatts' are conceived and applied in three TNC case studies. The initial findings indicate that variations in how TNCs approach SEP reflect differences in regulatory framework and business culture of their countries of origin.